Mayacaceae, a newly naturalized family for the Flora of China - Su, Fan; Guo, Ya-Nan; Zhou, Xin-Xin; Wang, Rui-Jiang (Phytotaxa, 2020)
Mayaca fluviatilis, an aquatic plant belonging to the monogeneric family Mayacaceae, native to tropical America, is reported here for the first time to be naturalized in Guangdong province, China. A morphological description, with detailed photographs, is provided for further taxonomic identification. Its invasive risk is evaluated according to its present propagation tendency.